Patient revisit interest: what extent quality affects hospital customer satisfaction? - Ade Ary Machmud; Nurdin Brasit; Maat Pono; Hendragunawan Sardjan Tahyf (International Conference On Association Of Indonesian Entrepreneurship Study Programs, 2024)
This study aims to examine the influence of service quality on patient satisfaction and interest in repeat visits at the Hasanuddin University Dental and Oral Education Hospital. Using a quantitative approach with a cross-sectional survey method, data was collected from 100 patients who had received services at the hospital. The research instrument in the form of a SERVQUAL questionnaire was used to measure five dimensions of service quality: tangibles, reliability, responsiveness, assurance, and empathy. Multiple regression analysis showed that service quality had a significant influence on patient satisfaction, with the dimensions of assurance and empathy contributing the most. In addition, patient satisfaction was shown to have a significant influence on revisit interest. These findings indicate that improved service quality can improve patient satisfaction, which in turn increases interest in repeat visits. Recommendations for hospital management include improving physical facilities, ongoing training for medical personnel, integration of health technology, and the development of an effective patient feedback system. With the implementation of these recommendations, it is hoped that the Hasanuddin University Dental and Oral Education Hospital can improve the quality of its services and strengthen patient loyalty.